2022
DOI: 10.24093/awej/vol13no4.25
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Continuous Corrective Feedback on Writings of Saudi EFL Students

Abstract: The present study aims to investigate the perceptions of EFL students on Corrective Feedback (C F) and to assess the efficacy of continuous explicit Corrective Feedback on the writings of the preparatory year female students of Umm Al Qura University in Saudi Arabia. The sample consisted of eleven students from an entire class who volunteered for the study. To reach the study’s objectives, an online survey was conducted to gain insight into how EFL students felt about receiving CF. Also, class observations and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This is confirmed by A. Chaudhary, who observed how students felt about receiving corrective feedback. The results of this study revealed, that corrective feedback is well suited for students, as they receive clear information about their mistakes (Chaudhary, 2022). However, a study by H. Bozorgian & Yazdani reveals the benefits of corrective feedback when mistakes are corrected (Bozorgian & Yazdani, 2021).…”
Section: Summary and Discussionmentioning
confidence: 78%
“…This is confirmed by A. Chaudhary, who observed how students felt about receiving corrective feedback. The results of this study revealed, that corrective feedback is well suited for students, as they receive clear information about their mistakes (Chaudhary, 2022). However, a study by H. Bozorgian & Yazdani reveals the benefits of corrective feedback when mistakes are corrected (Bozorgian & Yazdani, 2021).…”
Section: Summary and Discussionmentioning
confidence: 78%